Correlation of Justice in the Mahabharata Film with the Concept of Justice of Murtadho Muthahhari - Devi Rahmawati; Syafi’in Mansur; Agus Ali Dzawafi (Publikasi Indonesia, 2024)
The writing of this scientific paper discusses how the correlation between justice in the Mahabharata film and the concept of justice by Murtadho Muthahhari. Justice has become a topic of discussion by philosophers, religious scholars, politicians, and of course legal experts such as Murtadho Muthahhari. The purpose of this study is to find out the situation in the Mahabharata film, the concept of justice of Murtadho Muthahhari, and how it correlates with each other. The research method used is a qualitative method, with data sources obtained from the Mahabharata film, as well as books, and scientific works that support the research. After conducting this research, it can be found that there are similarities between justice in the Mahabharata film and the concept of justice by Murtadho Muthahhari. Murtadho Muthahhari explained that a person's good and bad deeds will not be separated from the judgment of God Almighty. In the story of Mahabharata which describes a person who does good, there will be a reward for his deeds. Likewise with evil deeds. Conclusion As in his story, the Pandavas who always do good will get a good reward from God, as well as Kaurawa who always does evil, will always get misfortune. This belief has been embraced by every religion, Hinduism, Buddhism, Christianity, and Islam as the religion that the author follows.